PARAMETERS OF UNCERTAINTY AMONG QUANTITY SURVEYORS FOR HERITAGE CONSERVATION REFURBISHMENT PROJECTS: THE CASE STUDY APPROACH - Ismail, Faridah; Isnaini Janipha, Nurul Afida; Jabar, Izatul Laili; Suhaili, Farah Nasiha (Journal of Surveying, Construction and Property, 2018)
Previous studies revealed that heritage conservation refurbishment projects contain more technical and economic uncertainty than new builds projects. Without a proper investigation by an experienced specialist, these uncertainties will remain unknown until the refurbishment works are carried out. Hence, it is insufficient for the Quantity Surveying (QS) to prepare tender documents for conservation work merely using standard documents for new building works. The objectives of this paper are to determine parameters of uncertainty that influence QS's services and to analyze the mitigation approaches in managing these uncertainties. Three projects were chosen as the Case Study in which the data was collected through questionnaire surveys distributed to five main stakeholders of the project. After the questionnaire distributed among the main consultants of the project, the same set of parameters of uncertainty were then verified with QS on which of those eleven (11) parameters of uncertainty that influence the QS's service. Case study analysis and content analysis are used in the data analysis. The results conclude that out of eleven (11) parameters of uncertainty; only three influenced QSS service in this project: availability of information; availability of material; and sufficiency of time allocation during the investigation phase. This study is intended to shed light for the QS to get an insight on heritage conservation refurbishment works as a whole and understand the main characteristic of the project which is complexity and uncertainty.